Development of an EPU vacuum system using lumped NEG-ion combination pumps. (January 2022) - Chan, C.K.; Chang, C.C.; Yang, I.C.; Cheng, C.M.; Chen, B.Y.; Shueh, C.; Cheng, Y.T.; Guo, Y.H.
Abstract: A vacuum design based on five lumped ZAO® non-evaporable getter (NEG) pumps (CapaciTorr® Z 200 × 2 and NEXTorr® Z 200 × 3) was developed to construct a vacuum system of elliptically polarized undulator (EPU). The vacuum tests, including measurements of the base pressure and the sorption capacity of CO, and the pressure-rise test on turning off the ion pumps, were performed to evaluate the vacuum performance of this design. Two such EPU vacuum systems were installed in the storage ring of Taiwan Photon Source (TPS) in 2020 and were conditioned with synchrotron radiation, but without baking. The experimental results show that their dynamic pressures achieved less than 3 × 10 −12  mbar mA −1 after an accumulated beam dose 100 A h. Highlights: A NEG cartridge-type vacuum system for an elliptically polarized undulator has been developed. The static pressure of the EPU vacuum system as low as 10 −10  mbar was achieved after a baking treatment. The dynamic pressures of two unbaked EPU chambers after receiving a beam-conditioning dose of 100 A h were both less than 3 × 10 −12  mbar mA −1 .